ANALISIS KADAR TANIN TOTAL EKSTRAK ETANOL BUNGA CENGKEH (Syzygium aromaticum L.) MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Mamat Pratama; Raiz Razak; Vivien Sandra Rosalina (Faculty of Pharmacy, Universitas Muslim Indonesia, 2019)
Clove flower (Syzygium aromaticum L.) contain saponins, tannins, alkaloids, glycosides and flavonoids. The research aimed to qualitatively and quantitatively determine the existence of tannins in ethanol extract of clove flower by UV-Vis Spectrophotometry. The extraction process used was maceration using ethanol of 30% with the yield value of 4.26%. The extract obtained was measured by UV-Vis Spectrophotometer at the maximum wavelength of 649.9 nm using tanic acid as the standard. The value of the measurement result of tannin content obtained in the ethanol extract of clove flower was 300.826 mg TAE/g extract or 30.0826% b/b TAE.